Karyomorphological Investigation of the Eight Species of the Muscari Genus Botryanthus Subgenus Growing in Turkey - Kiran, Yasar; Yildirim, Leyla; Dogan, Gulden; Eroglu, Huseyin; Pinar, Suleyman Mesut (Univ Tokyo Cytologia, 2023)
The chromosome numbers and karyotypes of eight species, the subgenus Botryanthus of the genus Muscari distributed in Turkey were analyzed. These taxa are M. adilii M.B. Guner & H. Duman, M. anatolicum Cowley & Ozhatay, M. bourgaei Baker, M. latifolium, J. Krik, M. inconstrictum Rech. f. M. microstomum P.H. Davis & D.C. Staurt, M. parviflorum Desf. and M. sandrasicum Karlen. Five of them (M. adilii, M. anatolicum, M. bourgaei, M. latifolium, M. sandrasicum) are endemic in Turkey. While the chromosome number of the examined taxa was generally determined as 2n= 2x= 18, the somatic chromosome number was determined as 2n= 4x= 36 in M. anatolicum and M. parviflorum. Haploid chromosome lengths varied from 26.00 mu m (M. adilii) to 101.74 mu m (M. parviflorum) among species. Karyotype analysis indicated that Muscari taxa generally have median point (M), median (m), submedian (sm), and subterminal (st) chromosomes. In addition, satellites were observed in two species, M. adilii and M. latifolium.
Keywords: Botryanthus; Muscari; Chromosome number; Karyomorphology; Turkey